Proximity of Cytomegalovirus-Specific CD8+ T Cells to Replicative Senescence in Human Immunodeficiency Virus-Infected Individuals - Heath, John Joseph; Fudge, Neva Jennifer; Gallant, Maureen Elizabeth; Grant, Michael David (Frontiers in Immunology, 2018)
Antiretroviral therapy, (ART) effectively extends the life expectancy of HIV-infected individuals, however, age-related morbidities have emerged as major clinical concerns. In this context, co-infection with cytomegalovirus (CMV) accelerates immune senescence and elevates risk for other age-related morbidities, possibly through increased inflammation. We investigated potential relationships between CMV memory inflation, immune senescence and inflammation by measuring markers of inflammation and telomere lengths of different lymphocyte subsets in HIV-infected individuals seropositive for anti-CMV antibodies. Our study cohort consists mainly of middle aged men who have sex with men (MSM) and heterosexuals who are stable under long term ART. Median levels of IL-6, TNF- and CRP were significantly higher in those co-infected with CMV. Lymphocyte telomere length in general correlated with age, but for 32/32 subjects tested, there was a consistent hierarchy of telomere lengths with CD8+ T cells’ shorter than the general lymphocyte population, CD57+CD8+ T cells’ shorter than CD8+ T cells’ and CMV-specific CD57+CD8+ T cells’ the shortest of all. Telomeres of HIV-specific CD8+ T cells were longer than those of CMV-specific CD8+ T cells in all cases tested and over 10 years, CMV-specific CD8+ T cell telomeres of 2 HIV-infected individuals eroded faster than those of HIV-specific CD8+ T cells. These data indicate that CMV-specific CD8+ T cells of HIV-infected individuals are the lymphocytes closest to telomere-imposed replicative senescence. Exhaustive proliferation of CMV-specific CD8+ T cells in HIV-infected individuals is a potential source of senescent lymphocytes affecting systemic immune function and inflammation.